2022
DOI: 10.1111/jam.15520
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of antibiotic-resistant bacteria on the clothes of nursery teachers in daycare centres

Abstract: Aims Childcare facilities act as microenvironments that facilitate and promote the selection, spread and transmission of antibiotic‐resistant micro‐organisms in the community. We focused on the study of antimicrobial resistance and genetic predispositions for β‐lactamase production in bacterial isolates from nursery teachers' clothing. Methods and Results Antimicrobial resistance of bacterial strains belonging to Enterobacteriaceae, Enterococcus, Staphylococcus spp., Pseudomonas spp. and Bacillus spp. isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Bacillus isolates are often susceptible to broad-spectrum antibiotics such as tetracycline, ciprofloxacin, and erythromycin, which are used to treat gastroenteritis caused by these bacteria. 13 Certain Bacillus species, such as B. cereus , are intrinsically resistant to β-lactams, except carbapenems 14 and can acquire resistance to antibiotics that are commonly used for infection therapy, such as ciprofloxacin, cloxacillin, erythromycin, tetracycline and streptomycin. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus isolates are often susceptible to broad-spectrum antibiotics such as tetracycline, ciprofloxacin, and erythromycin, which are used to treat gastroenteritis caused by these bacteria. 13 Certain Bacillus species, such as B. cereus , are intrinsically resistant to β-lactams, except carbapenems 14 and can acquire resistance to antibiotics that are commonly used for infection therapy, such as ciprofloxacin, cloxacillin, erythromycin, tetracycline and streptomycin. 15…”
Section: Discussionmentioning
confidence: 99%
“…The high resistance to penicillin and tetracyclines is not in agreement with a previous report, 13 which showed that Bacillus species are usually susceptible to broad-spectrum antibiotics such as tetracycline, ciprofloxacin and erythromycin, which are used in the treatment of gastroenteritis disease caused by these bacteria. However, certain species within the Bacillus genus, such as B. cereus , are intrinsically resistant to β-lactams, excluding carbapenems, 14 and can furthermore acquire resistance to commonly used antibiotics for the treatment of infections, such as ciprofloxacin, cloxacillin, erythromycin, tetracycline and streptomycin. 15 Most B. cereus isolates produce β-lactamases 16 and are resistant to penicillin and cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus isolates are often susceptible to broad-spectrum antibiotics such as tetracycline, ciprofloxacin, and erythromycin, and are used to treat gastroenteritis caused by these bacteria [16]. Certain Bacillus species, such as B. cereus, are intrinsically resistant to -lactams, except carbapenems [17] and can acquire resistance to commonly used antibiotics for infection therapy, such as ciprofloxacin, cloxacillin, erythromycin, tetracycline, and streptomycin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Textiles routinely harbour bacteria, encompassing Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa [1]. These bacterial strains are potential instigators of afflictions ranging from skin infections to urinary tract infections and respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%